Masculinity and Femininity in Yuriko Koike's Speech Style - Noorsanti, Parwati Hadi (Register Journal, 2021)
This study aims at describing Yuriko Koike’s speech style in conducting verbal interaction in public in relation to her profession as a politician and the Governor of Tokyo. In relation to gender stereotypes, women have a feminine speech style while men have a masculine speech style. The activities as a woman politician and leader will indeed affect Yuriko Koike’s language use in public communication, whether she fully incorporates a feminine style or also employs a masculine style. The data of this study is Yuriko Koike’s utterances in verbal interaction taken from YouTube, comprising informal talk shows, formal talk shows, and press conferences. The data are analyzed with the theories of gender and language, as well as speech style, proposed by Holmes and Stubbe (2003) and Talbot (2003). From the data obtained, it can be deduced that Yuriko Koike’s speech style is androgynous, which combines masculine and feminine speech styles. Her speech style, therefore, does not reflect the stereotypical style of the traditional Japanese women, which is polite, soft, unassertive, and indirect. Instead, Yuriko Koike is the depiction of the deconstruction of Japanese women’s communication today, by which she shows herself as a respected leader to her political opponents. Koike generally has a communication style of a leader, that is public, report, lecturing, referentially oriented, problem-solving, dominating, and task/outcome-oriented. Specifically, her masculine speech style includes direct, competitive, independent-autonomy, and dominant, while her feminine styles were effectively oriented-sympathy, rapport, intimacy-connection, collaborative, and supportive feedback.Keywords: speech style; feminine; masculine; Yuriko Koike